Screening of heat‐tolerant Ethiopian chickpea accessions: Assessment of phenological and agromorphological traits and genomic relationships. Issue 3 (14th September 2021) - Getahun, Tsegaye; Negash, Kassaye; Chang, Peter L.; von Wettberg, Eric; Carrasquilla‐Garcia, Noelia; Gaur, Pooran M.; Fikre, Asnake; Haileslassie, Teklehaimanot; Cook, Douglas; Tesfaye, Kassahun
Abstract: A major agronomic challenge for chickpea ( Cicer arietinum L.) production is temperatures above 35 °C, which causes reduced fertility and seed development. This study was aimed at assessing the phenotypic variation of chickpea genotypes under variable heat stress conditions. Chickpea genotypes were grown in heat‐stressed locations in both Ethiopia and India to assess phenotypic variation for heat tolerance. In addition, genomic relationships among the genotypes were assessed using genome‐wide single nucleotide polymorphism (SNP) markers. A total of 121 genotypes were assessed at three field sites in Ethiopia, under heat stress and nonstress conditions, and 57 genotypes were assessed under high‐heat‐stress conditions at the International Crops Research Institute for the Semiarid Tropics (ICRISAT) in Hyderabad, India. Data for five phenological and seven agromorphological traits were recorded. The results showed that the chickpea genotypes were severely affected by excessive heat at Hyderabad as compared with those planted under non‐heat‐stress conditions in Debre Zeit, Ethiopia. At extremely high temperatures, chickpea plants exhibited reduced floral initiation, arrested seed and pod development, shortened life cycles, and reduced plant height, seed size, grain yield, and yield‐related traits. Across stressed and nonstressed environments, there were highly significant differences among the genotypes for most of the traits (ANOVA, P ≤ .001). Under heat‐stressed environments, DZ‐Cr‐0034 was found to be a highly tolerant, whereas DZ‐Cr‐0026 was found to be a highly sensitive genotype. Genetic relationships among the genotypes were determined using 5, 722 SNPs, revealing a single group of Ethiopian genotypes with small number of cultivars showing introgression from Middle Eastern germplasm. This study clearly demonstrated that there is genetic variability in chickpea for heat tolerance that can be harnessed to meet expected shifts towards warmer climatic conditions. Core Ideas: Heat‐tolerant chickpea genotypes were screened under three heat‐stressed environments. Chickpea genotypes were evaluated under non‐heat‐stress environment for comparison. Genetic variability of genotypes for phenological and agromorphological traits were determined. The correlations among traits and genotypes were demonstrated. The genomic relations among the genotypes were assessed using SNPs.